The role of anaerobic bacteria in the cystic fibrosis airway. Issue 6 (November 2016) - Sherrard, Laura J.; Bell, Scott C.; Tunney, Michael M.
Abstract : Purpose of review: Anaerobic bacteria are not only normal commensals, but are also considered opportunistic pathogens and have been identified as persistent members of the lower airway community in people with cystic fibrosis of all ages and stages of disease. Currently, the role of anaerobic bacteria in cystic fibrosis lower airway disease is not well understood. Therefore, this review describes the recent studies relating to the potential pathophysiological role(s) of anaerobes within the cystic fibrosis lungs. Recent findings: The most frequently identified anaerobic bacteria in the lower airways are common to both cystic fibrosis and healthy lungs. Studies have shown that in cystic fibrosis, the relative abundance of anaerobes fluctuates in the lower airways with reduced lung function and increased inflammation associated with a decreased anaerobic load. However, anaerobes found within the lower airways also produce virulence factors, may cause a host inflammatory response and interact synergistically with recognized pathogens. Summary: Anaerobic bacteria are potentially members of the airway microbiota in health but could also contribute to the pathogenesis of lower airway disease in cystic fibrosis via both direct and indirect mechanisms. A personalized treatment strategy that maintains a normal microbial community may be possible in the future.